Contract for Peace: Peace Agreements and its Security Implication - Sharma, Rajendra (Journal of APF Command and Staff College, 2020)
Negotiated settlements have been increasingly accepted as the preferred way of ending civil wars. Studies show that only 50 percent of negotiated settlements last beyond five years, while in others, negotiated settlements have been shown to keep the peace for only three and half years. Contrary to this, the peace agreements/understandings were universally considered as the pivotal blue print for conflict transformation and peace buildings. In our case, the management of arms and armies, reintegration of few former rebels in the national army, promulgation of the constitution from the constituent assembly etc. are the crucial tasks of the peace process. In this context, this paper highlights the major peace agreements (2005-2010) reached between the then Communist Party of Nepal (CPN)-Maoist and the seven parliamentary party alliance’s government and simultaneously tries to analyze these agreements’ influence on security. The 12-point understanding of 2005 concluded in New Delhi is the guiding framework of the Nepalese peace process and has its geostrategic implication as well. Likewise, the Comprehensive Peace Accord (CPA) of 2006 is a milestone in bringing about an end to the decade of old civil war and beginning an inclusive, secular, peaceful and democratic nation-building process. Despite everything, delaying the transitional justice process and staling the social reconciliation can be the potential reason for a reprisal of conflict